Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,ĐK:x\ge-\dfrac{3}{2}\\ PT\Leftrightarrow\sqrt{x+1}-2+\sqrt{2x+3}-3=0\\ \Leftrightarrow\dfrac{x-3}{\sqrt{x+1}+2}+\dfrac{2\left(x-3\right)}{\sqrt{2x+3}+3}=0\\ \Leftrightarrow\left(x-3\right)\left(\dfrac{1}{\sqrt{x+1}+2}+\dfrac{2}{\sqrt{2x+3}+3}\right)=0\)
Dễ thấy ngoặc lớn luôn >0
Do đó \(x-3=0\Leftrightarrow x=3\)
\(b,ĐK:x\le-1\\ PT\Leftrightarrow\sqrt{3x^2+4x+1}=x-1\\ \Leftrightarrow3x^2+4x+1=x^2-2x+1\\ \Leftrightarrow2x^2+6x=0\\ \Leftrightarrow2x\left(x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\left(ktm\right)\\x=-3\left(tm\right)\end{matrix}\right.\)
a.
ĐKXĐ: \(x\ge-1\)
\(\sqrt{x+1}+\sqrt{2x+3}=5\)
\(\Leftrightarrow\sqrt{x+1}-2+\sqrt{2x+3}-3=0\)
\(\Leftrightarrow\dfrac{x-3}{\sqrt{x+1}+2}+\dfrac{2\left(x-3\right)}{\sqrt{2x+3}+3}=0\)
\(\Leftrightarrow\left(x-3\right)\left(\dfrac{1}{\sqrt{x+1}+2}+\dfrac{2}{\sqrt{2x+3}+3}\right)=0\)
\(\Leftrightarrow x-3=0\) (do \(\dfrac{1}{\sqrt{x+1}+2}+\dfrac{2}{\sqrt{2x+3}+3}>0\))
\(\Leftrightarrow x=3\)
ĐK : x >= 2
\(x-\frac{7}{4}-\sqrt{x-2}=0\Leftrightarrow x-\frac{7}{4}=\sqrt{x-2}\)
\(\Leftrightarrow4x-7=4\sqrt{x-2}\Leftrightarrow16x^2-56x+49=16x-32\)
\(\Leftrightarrow16x^2-72x+81=0\Leftrightarrow\left(4x-9\right)^2=0\Leftrightarrow x=\frac{9}{4}\left(tm\right)\)
a.ĐKXĐ;\(\hept{\begin{cases}x\ge0\\x\ne4\end{cases}}\)
b.P=\(\frac{\sqrt{x}+1}{\sqrt{x}-2}+\frac{2\sqrt{x}}{\sqrt{x}+2}+\frac{2+5\sqrt{x}}{4-x}\)=\(\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+2\right)+2\sqrt{x}\left(\sqrt{x}-2\right)-2-5\sqrt{x}}{x-4}\)
=\(\frac{3x-6\sqrt{x}}{x-4}=\frac{3\sqrt{x}.\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)=\(\frac{3\sqrt{x}}{\sqrt{x}+2}\)
c.P=2\(\Leftrightarrow\frac{3\sqrt{x}}{\sqrt{x}+2}=2\Leftrightarrow3\sqrt{x}=2\sqrt{x}+\text{4}\)\(\Leftrightarrow\sqrt{x}=4\Leftrightarrow x=16\)
Vậy x=16
Bài 1:
ĐKXĐ: $3-2x\geq 0\Leftrightarrow x\leq \frac{3}{2}$
Bài 2:
a. ĐKXĐ: $x\geq \frac{1}{3}$
PT $\Leftrightarrow 3x-1=2^2=4$
$\Leftrightarrow x=\frac{5}{3}$ (tm)
b. ĐKXĐ: $x\geq 2$
PT $\Leftrightarrow \sqrt{x-2}+2\sqrt{x-2}=6$
$\Leftrightarrow 3\sqrt{x-2}=6$
$\Leftrightarrow \sqrt{x-2}=2$
$\Leftrightarrow x-2=4$
$\Leftrightarrow x=6$ (tm)
\(a,ĐK:x\ge1\\ PT\Leftrightarrow x-1+5x-1-2\sqrt{\left(x-1\right)\left(5x-1\right)}=3x-2\\ \Leftrightarrow2\sqrt{5x^2-6x+1}=3x\\ \Leftrightarrow4\left(5x^2-6x+1\right)=9x^2\\ \Leftrightarrow11x^2-24x-4=0\\ \Leftrightarrow\left(x-2\right)\left(11x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=2\left(tm\right)\\x=\dfrac{2}{11}\left(ktm\right)\end{matrix}\right.\Leftrightarrow x=2\)
\(b,ĐK:-1\le x\le1\)
Đặt \(\left\{{}\begin{matrix}\sqrt{1-x}=a\\\sqrt{1+x}=b\end{matrix}\right.\left(a,b\ge0\right)\), PTTT:
\(a+b=ab+1\\ \Leftrightarrow\left(b-1\right)-a\left(b-1\right)=0\\ \Leftrightarrow\left(1-a\right)\left(b-1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}a=1\\b=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}1-x=1\\1+x=1\end{matrix}\right.\Leftrightarrow x=0\left(tm\right)\)